Kition-Bamboula VIII Le port de guerre de Kition - Callot, Olivier; Fourrier, Sabine; Yon, Marguerite (Archéologie(s), 2022)
From 1984 to 1999, the French archaeological mission of Kition, under the supervision of Marguerite Yon, conducted extensive excavations to the north of the Bamboula sanctuary. These excavations revealed the remains of shipsheds of the Classical period, among the best preserved in the Mediterranean, which opened to the north on a closed harbour basin. This book offers a detailed and cross-cutting study of this outstanding discovery: the building is contextualized in its paleoenvironment (both at the local and regional levels), the chronology of its different phases is established, its architecture is carefully described and restored for the missing parts (superstructure). Finally, we assess the importance of this military harbour for the history of Kition, Cyprus and the Eastern Mediterranean, at the time of the Classical kingdom (4th century BC) and at the beginning of the Hellenistic period. The volume is completed by a study of the ceramics from the Roman period discovered in the filling of the basin. The archives of the excavation are available on the open access web-portal chypre.mom.fr.